Pengaruh Kepemimpinan Instruksional Kepala Sekolah, Iklim Organisasi dan Motivasi Kerja Guru Terhadap Etos Kerja Guru SMA Negeri Di Kota Palangka Raya - Septina Wijayanti; Ahmad Suriansyah; Wahyu Wahyu (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Abstract: Teachers' work ethic plays an important role in shaping the character of students. One of the factors that affects it is the leadership of the principal, especially instructional leadership that can create a positive organizational climate and increase work motivation. This study aims to analyze the influence of instructional leadership and organizational climate on teachers' work ethic, both directly and through work motivation at SMA Negeri Palangka Raya City. This study uses a quantitative approach with a population of 527 teachers from 10 public high schools in Palangka Raya City, and a sample of 227 teachers taken proportionally using random sampling. Data is collected through a Likert questionnaire that has been tested for validity and reliability. Data analysis was carried out using path analysis and multiple regression. The results of the study showed: (1) an overview of the principal's instructional leadership, organizational climate, teacher competence, and work ethic; (2) the instructional leadership of the principal has a direct effect on the work ethic of teachers; (3) the organizational climate has a direct effect on the work ethic of teachers; (4) teachers' work motivation has a direct effect on teachers' work ethic; (5) instructional leadership and organizational climate have a direct effect on teachers' work motivation; (6) there is an indirect influence of instructional leadership and organizational climate on work ethic through work motivation. These findings show that teachers' work ethic is influenced by the quality of the principal's leadership, a conducive organizational climate, and high work motivation. These results emphasize the importance of leadership that is not only administrative, but also encourages communication, appreciation, and individual development. It is suggested that strengthening the organizational climate and teachers' work motivation be made into a sustainable program. This research also opens up opportunities for further study to explore teachers' work ethic more deeply. Keywords: Instructional Leadership; Organizational Climate; Work Motivation; Teacher Work Ethic. Abstrak: Etos kerja guru berperan penting dalam membentuk karakter peserta didik. Salah satu faktor yang memengaruhinya adalah kepemimpinan kepala sekolah, khususnya kepemimpinan instruksional yang dapat menciptakan iklim organisasi positif dan meningkatkan motivasi kerja. Penelitian ini bertujuan menganalisis pengaruh kepemimpinan instruksional dan iklim organisasi terhadap etos kerja guru, baik secara langsung maupun melalui motivasi kerja di SMA Negeri Kota Palangka Raya. Penelitian ini menggunakan pendekatan kuantitatif dengan populasi 527 guru dari 10 SMA Negeri di Kota Palangka Raya, dan sampel 227 guru yang diambil secara proporsional menggunakan random sampling. Data dikumpulkan melalui angket Likert yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan menggunakan analisis jalur dan regresi berganda. Hasil penelitian menunjukkan: (1) gambaran kepemimpinan instruksional kepala sekolah, iklim organisasi, kompetensi guru, dan etos kerja guru; (2) kepemimpinan instruksional kepala sekolah berpengaruh langsung pada etos kerja guru; (3) iklim organisasi berpengaruh langsung pada etos kerja guru; (4) motivasi kerja guru berpengaruh langsung pada etos kerja guru; (5) kepemimpinan instruksional dan iklim organisasi berpengaruh langsung pada motivasi kerja guru; (6) terdapat pengaruh tidak langsung kepemimpinan instruksional dan iklim organisasi terhadap etos kerja melalui motivasi kerja. Temuan ini menunjukkan bahwa etos kerja guru dipengaruhi oleh kualitas kepemimpinan kepala sekolah, iklim organisasi yang kondusif, dan motivasi kerja yang tinggi. Hasil ini menekankan pentingnya kepemimpinan yang tidak hanya bersifat administratif, tetapi juga mendorong komunikasi, apresiasi, dan pengembangan individu. Disarankan agar penguatan iklim organisasi dan motivasi kerja guru dijadikan program berkelanjutan. Penelitian ini juga membuka peluang studi lanjutan untuk mengeksplorasi etos kerja guru lebih mendalam. Kata kunci: Kepemimpinan Instruksional; Iklim Organisasi; Motivasi Kerja; Etos Kerja Guru